Influence of sheep manure, vermicompost and biofertilizer on growth, yield and profitability of cumin (Cuminum cyminum L.) production - Malhotra S K, Mehta R S, Anwer M M, (Journal of Spices and Aromatic Crops, 2012)
A field study on effect of various sources of organic manure (sheep manure and vermi compost) with and without biofertilizer (Azotobacter sp.) on performance of cumin (Cuminum cyminum L.) was conducted at Ajmer (Rajasthan) during rabi 2003, 2004 and 2005. Application of biofertilizer alone as well as in combination with sheep manure, vermicompost and recommended doses of fertilizer resulted in higher growth, yield attributes and yield over absolute control. The association of biofertilizers with all sources of nutrients proved beneficial and resulted in higher growth and yield. Application of recommended doses of fertilizer with seed inoculation by biofertilizer proved to be superior for realizing higher net return and benefit:cost ratio.